Human Resource Diversity Management and Knowledge Sharing: Gender Perspectives from Three Countries on The Asian Continent (Thailand, Japan, Indonesia) - Fazriyani, Fanesha; Sanusi, Fauji; Damarwulan, Liza Mumtazah (Journal of Applied Business, Taxation and Economics Research, 2024)
This study reviews the literature on human resource diversity management and knowledge sharing. 11 international journals were taken as samples and then identified and analyzed. The author examines the implementation of human resource diversity management and knowledge sharing in several countries. This research study shows the importance of human resource diversity management (HRD) in encouraging knowledge sharing in the workplace and how Thailand, Japan, and Indonesia implement gender equality in organizations. The analysis results in this study concluded from the three countries that the role of women in organizations is very beneficial for increasing knowledge and the smoothness of an organization and can develop the Company's performance. However, it is still dominated by men. This article contributes to the literature on human resource diversity management and knowledge sharing, which will be a reference for future research.